Antagonistas de CCR5 en la infección por virus de inmunodeficiencia humana (VIH): aspectos generales y tropismo viral - Ferrer C., Pablo; Rodríguez M., Consuelo; Tordecilla F., Rocío; Guzmán M., María A.; Afani S., Alejandro (Revista Hospital Clínico Universidad de Chile, 2012)
The human immunodeficiency virus (HIV) is highly mutagenic and generates resistance to the available anti-HIV drug therapies. Because of this a new family of anti-HIV drugs therapies has been created. These new drugs have different mechanisms of action. The HIV entry inhibitors act through specifics correceptors CCR5/CXCR4 localized on CD4 + cells. The HIV tropism determination (phenotypic and genotypic assays) arises to guide therapeutic decisions and define to which patients this treatment will be successful. Genotypic assays are technically advantageous and represent a more feasible alternative to phenotypic assays. The genotypic tropism assay from proviral DNA would have a greater impact, because of its ability to detect tropism in those patients with low or undetectable viral load.